(untitled) (Journal of Philosophy Culture and Political Science, 2018)
The article deals with the essence of innovation and its role in the modernization of society. The authors consider the essence of innovation culture. The authors reveal its role in a modernizing society. The article describes the culture of innovation. The significance of the role of innovative culture is considered. The authors examine the nature and characteristics of some of the innovative qualities of a person. Attention is paid to the impact of an innovation culture on the position and activity of the person. The authors draw attention to the impact of an innovative culture on the modification of education. The article describes the basic functions of the innovative culture. Key words: innovation, innovative culture, innovative person, innovative qualities, education and innovation, functions of innovative culture.